Marketing Management Of Hajj Savings Products At Bank Syariah Indonesia At BSI KCP Bandung Majalaya - Salma Aulia Hanifah (Penerbit Hellow Pustaka, 2023)
This research was conducted to determine the marketing management of Hajj savings products carried out by Bank Syariah Indonesia at the KCP Bandung Majalaya branch office. The aim is to know how marketing management is carried out to make people around the branch office interested and open a Hajj savings account. Marketing is very important in a company office, where the company office must learn how to market its products that are adapted to the conditions and circumstances of the community around its branch office. The aim of this marketing is so that people know, understand and are interested in opening Hajj savings for their future. By marketing the product, of course it must be matched with the quality of the product being marketed, where the Hajj savings product at Bank Syariah Indonesia has its own advantages in attracting potential customers. Bank Syariah Indonesia has attracted many customers in the last two years, which is a good start for Bank Syariah Indonesia. The target target for this marketing is all groups, namely from young people to the elderly.